2019
DOI: 10.2147/clep.s201614
|View full text |Cite
|
Sign up to set email alerts
|

<p>Polypharmacy and injurious falls in older adults: a nationwide nested case-control study</p>

Abstract: Objective To determine whether or not the exposure to multiple drugs (polypharmacy) increases the risk of fall-related injury among older adults, beyond the effect of fall-risk increasing drugs and chronic multimorbidity. Methods Nested case-control study using linked register data with national coverage in Sweden. We defined cases as older adults (≥70 years) who had an incident non-elective admission due to a fall between 1 January and 31 December 2013. Cases were matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 63 publications
3
31
1
1
Order By: Relevance
“…The prevalence of suspected medication-related falls is about 41% [ 555 ] to 49% [ 556 ]. Increased risk of falls was documented in users of anxiolytics/hypnotics, opioids, sedatives, antihypertensives (especially alpha-blockers), antidepressants, antiparkinsonian medications, antiepileptics and antiarrhythmics [ 557 , 558 , 559 , 560 , 561 , 562 , 563 , 564 , 565 , 566 , 567 , 568 , 569 , 570 , 571 , 572 , 573 , 574 , 575 , 576 , 577 , 578 , 579 , 580 , 581 , 582 , 583 ]; polypharmacy is strongly associated with injurious falls and fractures [ 574 , 582 , 584 , 585 , 586 , 587 , 588 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…The prevalence of suspected medication-related falls is about 41% [ 555 ] to 49% [ 556 ]. Increased risk of falls was documented in users of anxiolytics/hypnotics, opioids, sedatives, antihypertensives (especially alpha-blockers), antidepressants, antiparkinsonian medications, antiepileptics and antiarrhythmics [ 557 , 558 , 559 , 560 , 561 , 562 , 563 , 564 , 565 , 566 , 567 , 568 , 569 , 570 , 571 , 572 , 573 , 574 , 575 , 576 , 577 , 578 , 579 , 580 , 581 , 582 , 583 ]; polypharmacy is strongly associated with injurious falls and fractures [ 574 , 582 , 584 , 585 , 586 , 587 , 588 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Moreover, age-related changes in pharmacodynamics and pharmacokinetics contribute to stronger effects of many drugs and therefore the risk of negative outcomes [9]. In epidemiological studies, polypharmacy has been associated with enhanced risks of adverse events in older people which comprise falls, hospitalization and higher mortality [10][11][12][13]. Increased chances of developing cognitive disturbances and decline have also been linked with inappropriate use of multiple medications in older AGING adults [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A review of relevant literature showed polypharmacy to have a variable link to falling in older adults [ 66 ]. However another, nationwide nested case-control study found a direct relationship between polypharmacy and injurious falls [ 67 ].…”
Section: Discussionmentioning
confidence: 99%